Non-suicidal self-injury in the COVID-19 pandemic: results from cross-sectional surveys among Brazilian adults from 2020 to 2023 - Faro, Andre; Lisboa, Walter; Silva-Ferraz, Brenda F.; Falk, Derek (Frontiers in Psychology, 2024)
The multilevel psychosocial stressors associated with COVID-19 pandemic set the stage to investigate risk factors and groups susceptible for non-suicidal self-injury (NSSI). A national sample of 9,929 Brazilian adults aged 36.1 years on average participated in the study. Cross-sectional data were collected in 2020, 2021, 2022, and 2023. NSSI levels were considered high in the total sample (13.2%) when compared to other studies in this context. The variables with the highest explanatory power in the regression models were age, anxiety, and depression. The main risk factors were being younger, living in the South or Southeast regions of Brazil, having lower educational attainment, and having higher rates of anxiety and depression. Respondents had the highest probability of NSSI in 2022. The sustained higher rates of NSSI in 2023 compared to the beginning of the pandemic underscores the need for continuous monitoring and the development of preventive actions for selfinjurious behaviors.